Cancers in Australia in 2010 attributable to and prevented by the use of combined oral contraceptives. (October 2015) - Jordan, Susan J.; Wilson, Louise F.; Nagle, Christina M.; Green, Adele C.; Olsen, Catherine M.; Bain, Christopher J.; Pandeya, Nirmala; Whiteman, David C.; Webb, Penelope M.
Abstract Objectives: To estimate the proportion and number of cancers occurring in Australia in 2010 attributable to combined oral contraceptive pill (OCP) use. Methods: We estimated the population attributable fraction (PAF) for cancers causally associated with combined OCP use (breast, cervix), and the proportion of endometrial and ovarian cancers prevented (prevented fraction [PF]). We used standard formulae incorporating prevalence of combined OCP use in the Australian population, relative risks of cancer associated with this exposure and cancer incidence. Results: An estimated 105 breast and 52 cervical cancers (0.7% and 6.4% of each cancer, respectively) in Australia in 2010 were attributable to current use of combined OCP. Past combined OCP use was estimated to have prevented 1, 032 endometrial and 308 ovarian cancers in 2010, reducing the number of cancers that would otherwise have occurred by 31% and 19%, respectively. Conclusions: A small proportion of breast and cervical cancers is attributable to combined OCP use; OCP use is likely to have prevented larger numbers of endometrial and ovarian cancers. Implications: Women seeking contraceptive advice should be told of potential adverse effects, but should also be told that – along with reproductive health benefits – combined OCP use can reduce long‐term risks of ovarian and endometrial cancers.